DEFINITION OF THE USE OF THE LEXEME PLEASE IN EXPLANATORY DICTIONARIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents various definitions of the lexeme request in explanatory dictionaries and examples of their corresponding meanings. Definitions of this lexeme in explanatory dictionaries in Russian, English, Uzbek and other languages are shown.